Art and poetry on archive rails. A branch line that connects territories and communities - Rasic, María Eugenia (Universidad Nacional del Litoral, 2019)
The next article proposes to establish a contact between two territories of the province of Buenos Aires that, although they have never been directly connected by any branch of the railroad, they should be from the reading made from the archive regarding the poetic actions and artistic developed by the community that lives in these points of the map. These actions, which have an overwhelming archival power, have been carried out, and many of them still continue, within the framework of the following cultural projects: Estación Pringles, located mainly in the stations of the Party of Colonel Pringles, and Proyecto Hermosura, located at the Cura-Malal station, Partido de Coronel Suárez. As you will see below, the archifilological look on the poetic, artistic and collective actions, deployed in the territory and the landscape that composes it, will recover before your eyes the sparks of the train that passed through there, as well as the flashes of a latent and inappropriate community.